The Platformization of Literary Practices in Lives by Clubinho do King on YouTube - Da Silva Pochmann, Pâmela (2023)
The study, with the theme of platformization reading practices on YouTube, aims to understand the process of platformization reading practices in the lives of Clubinho do King. For this, it mobilizes the concepts of cultural platformization, influencers, YouTube and reading. The methodology involves the analysis by platformization bias in four readings of Clubinho do King and in the comments, in two specific lives. The results identify that aspects of platformization affect how the practice is consumed and disseminated on YouTube and that features such as the hashtag, external referral links and the “@” facilitate handling by the cultural producer and users.